Preparation method of micro-led full-color display device based on open microfluidic technology
Patent Information
- Application Number
- CN202310783420.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-06-29
AI Technical Summary
In existing Micro-LED full-color display devices, during the deposition process of quantum dot solution, the thickness of the quantum dot pattern becomes uneven after the solvent evaporates, affecting the color purity and light emission efficiency of photoluminescence color conversion, and easily causing light crosstalk and color mixing phenomena.
Open microfluidic technology is used to prepare hollow glass microchannels. By combining liquid-repellent chemical substances to restrict the flow of quantum dot solution, the solvent evaporates and is concentrated in a patterned groove array. Combined with a filter encapsulation layer to prevent light crosstalk, spontaneous deposition of quantum dot patterns and efficient color conversion are achieved.
It achieves controllable thickness of quantum dot patterns, reduces color mixing, improves color purity and light utilization, is suitable for mass production, and enhances the color conversion efficiency and purity of display devices.
Smart Images

Figure CN116825933B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of quantum dot color conversion layer display, specifically relating to a method for fabricating a Micro-LED full-color display device based on open microfluidic technology. Background Technology
[0002] Micro-LEDs are a novel display technology applicable to automotive displays, wearable devices, AR / VR displays, and other fields. Currently, achieving full-color displays using mass transfer technology to integrate red, green, and blue chips suffers from low yield and high cost. Therefore, combining quantum dot color conversion layers with Micro-LEDs to achieve full-color displays has attracted increasing attention. The fabrication of quantum dot color conversion layers typically employs photolithography, inkjet printing, and microfluidics. Compared to mass transfer technology, quantum dot color conversion layer technology offers significant advantages such as lower cost, higher resolution, and shorter processing time. Quantum dot materials, with their high absorption coefficient, narrowband emission, high photoluminescence yield, and ease of processing, are suitable materials for manufacturing high-resolution patterned color conversion layers for display applications. In the quantum dot color conversion layer method, quantum dot patterns need to be deposited on the device surface or substrate. The quantum dot solution includes solute and solvent. When the quantum dot solution is deposited, the quantum dot solute remaining after the solvent evaporates is an important component of color conversion. The pattern thickness and uniformity of the solute after quantum dot evaporation, as well as the purity of the color after photoluminescence color conversion, have a significant impact on the overall performance of Micro-LED full-color display devices.
[0003] In the application of quantum dot materials in full-color displays, the thickness of the quantum dot color conversion layer pattern plays a crucial role, determining the purity and light extraction efficiency of the colors after photoluminescence color conversion. The thickness of the quantum dot pattern after solvent evaporation in the quantum dot solution significantly affects the color conversion effect of the photoexcited quantum dot pattern. If the quantum dot pattern is too thin, it easily causes leakage of the excitation light source, affecting color purity; if the quantum dot pattern is too thick, the light after photoluminescence color conversion will be self-absorbed by the quantum dot pattern, thus reducing light extraction efficiency. These issues inevitably affect the light extraction and light quality of Micro-LED light sources in achieving full-color display by exciting the quantum dot color conversion layer. Secondly, a small number of quantum dots deposited between patterned array sub-pixels can easily cause light crosstalk and color mixing phenomena between sub-pixels when the quantum dots are photoexcited to achieve photoluminescence, greatly affecting the effect of the full-color display image. Summary of the Invention
[0004] This invention addresses the shortcomings of existing technologies by providing a method for fabricating Micro-LED full-color display devices based on open microfluidic technology. The method employs open microfluidic technology to fabricate perforated glass microchannels that can be used for quantum dot solution deposition. By combining the "liquid-repellent" properties of relevant groups in the liquid-repellent chemical substances, the flow of the quantum dot solution is restricted, allowing the quantum dot solvent to evaporate and concentrate in a patterned groove array. Micro-LED blue light excites the quantum dot pattern in the grooves to achieve full-color display.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows:
[0006] A method for fabricating a Micro-LED full-color display device based on open microfluidic technology specifically involves fabricating a quantum dot color conversion layer and a filter encapsulation layer, and bonding the two sides of the quantum dot color conversion layer to the Micro-LED light-emitting chip array and the filter encapsulation layer, respectively; wherein the fabrication of the quantum dot color conversion layer includes the following steps:
[0007] 1) A transparent array of grooves is fabricated on the first substrate;
[0008] 2) Perform a hydrophobic treatment on the surface outside the groove array of the first substrate;
[0009] 3) Provide a second substrate, in which hollowed-out microchannels are formed;
[0010] 4) Bond the first substrate and the second substrate together so that the hollowed-out microchannels and grooves cooperate to form a microchannel pathway;
[0011] 5) Quantum dot solution is injected into the microchannel pathway. During the evaporation process, the quantum dot solution gradually deposits in the groove to form quantum dot units;
[0012] 6) Peel off the second substrate;
[0013] The filter encapsulation layer is prepared by forming a filter array on a third substrate, wherein the filter array corresponds one-to-one with the groove array, and a shielding layer is provided between adjacent filters.
[0014] Optionally, the first substrate includes a first glass substrate and a metal mask layer disposed on the first glass substrate. In step 1), the fabrication of the groove array includes:
[0015] 1.3) The metal mask layer is patterned using etching technology to form an array of openings;
[0016] 1.4) The first glass substrate is etched using a patterned metal mask layer as a mask to form the transparent groove array.
[0017] Optionally, the depth of the groove is 2-10 micrometers.
[0018] Optionally, the metal mask layer is a chromium layer with a thickness of 20nm-50nm. In step 2), photoresist is filled in the groove array, the first substrate is placed in a reaction vessel with a trichloro(1H,1H,2H,2H-tetrafluorooctyl)silane atmosphere, and reacted at 50-70°C for 2-3 hours to modify the surface of the chromium layer to be hydrophobic, and then the photoresist is removed.
[0019] Optionally, the second substrate is a glass substrate. In step 3), a femtosecond laser is first used to laser-induced denaturation of the microchannel wiring preset area of the second substrate, and then the second substrate is etched in hydrofluoric acid solution to form the hollowed-out microchannel.
[0020] Optionally, the thickness of the second substrate is 350-550 μm, the pulse energy of the femtosecond laser is 10-50 μJ, the laser scanning speed is 1-3 mm / s, the pulse width is 2-5 wfs, and the dot pitch is 3-8 μm.
[0021] Optionally, the hollowed-out microchannel includes several arranged strip channels, with each pair of strip channels forming a unit, and a space for one strip channel left between adjacent units. The strip channels of adjacent units are connected in pairs through curved channels to form two parallel microchannel pathways; in step 4), each strip channel corresponds to a row of grooves in the groove array.
[0022] Optionally, the width of the strip channel matches the width of the groove, and the length covers the row length of the groove array, and the width of the curved channel is 20% to 50% of the width of the strip channel.
[0023] Optionally, in step 5), one of the two microchannel pathways is filled with a red quantum dot solution, and the other is filled with a green quantum dot solution; the Micro-LED light-emitting chip array is a blue light-emitting chip.
[0024] The above describes the fabrication of a Micro-LED full-color display device based on open microfluidic technology.
[0025] The quantum dot solution is a solution formed by quantum dots and a solvent, including an aqueous solution of quantum dots or a chloroform solution of quantum dots; it can also be a composite solution of quantum dots, i.e., an oil-soluble or water-soluble composite solution formed by mixing quantum dots, polymers, and solvents. Water-soluble solutions include a mixture of quantum dots and ethanol, where ethanol can be replaced by hydrophilic solvents such as water, methanol, or isopropanol. Oil-soluble solutions include quantum dots with organic solvents such as toluene, xylene, anisole, n-hexane, cyclohexane, and tetradecane. The aforementioned quantum dots mainly include CdSe, ZnSe, CdTe, CdS, CuInSe, InP, PbS, and CuInS cores and their core-shell structures. In this embodiment, the red and green quantum dot solutions mainly use a mixture of CdSe and cyclohexane, where the concentration of red quantum dots is 0.15-0.5 mol / L, the concentration of green quantum dots is 0.2-0.7 mol / L, the diameter of the red quantum dot material is 8-10 nm, and the diameter of the green quantum dot material is 3-7 nm.
[0026] The beneficial effects of this invention are as follows:
[0027] (1) A microchannel hollow substrate is prepared for the deposition of quantum dot solution. The quantum dot solution is deposited into a patterned groove array through the hollow microchannels. Since the microchannels are hollow substrates in contact with air, the solvent of the quantum dots evaporates quickly, and the concentration of quantum dots gradually increases with solvent evaporation, which helps the solute to deposit into the groove array. Due to the different surface compositions inside and outside the groove structure, the high concentration of quantum dot solution is selectively deposited in the grooves, so a quantum dot patterned array can be obtained easily and spontaneously. The thickness of the quantum dot pattern is controllable, and multiple fillings of quantum dot solution can be achieved without rebonding, simplifying the subsequent optimization process. This ensures that the thickness of the quantum dots in the patterned area can fully absorb the excitation light source without self-absorbing light, improving the light utilization rate of the excitation light source and enhancing the color conversion efficiency. The hollow microchannels are independent, so different quantum dots can be deposited simultaneously and quickly, reducing the occurrence of color mixing and improving color purity.
[0028] (2) Using hollow microchannels instead of semi-closed microchannels can reduce the blockage caused by quantum dot solutions of different properties in semi-closed microchannels. It can also reduce the difficulty of injecting quantum dot solutions due to the pressure difference between the inside and outside of the narrow channel. Hollow microchannels can achieve high bonding between the microchannels and the bottom groove array without the need for marking, which improves the preparation rate and is suitable for the preparation of large-scale sub-pixel quantum dot color conversion layers.
[0029] (3) The masking layer isolates the filter pattern to realize the encapsulation layer preparation, which increases the color contrast during display and reduces the generation of stray light. This is beneficial to improve the quality of quantum dot color conversion light and prevent light crosstalk between sub-pixels, thereby improving the purity of color. Attached Figure Description
[0030] Figure 1 This is a cross-sectional schematic diagram of the first substrate in step 2 of the embodiment;
[0031] Figure 2 This is a top view schematic diagram of the patterned first substrate in step 3 of the embodiment;
[0032] Figure 3 This is a schematic cross-sectional view of the first substrate with a patterned glass groove array in step 4 of the embodiment.
[0033] Figure 4 This is a top view of the photoresist-filled groove array in step 5 of the embodiment;
[0034] Figure 5 This is a schematic diagram of the laser-induced glass deformation traces in step 7 of the embodiment;
[0035] Figure 6 This is a top view of the perforated glass microchannel in step 7 of the embodiment;
[0036] Figure 7 This is a top view schematic diagram of the bonding of a patterned first substrate to a second glass substrate with hollowed-out microchannels in step 8 of the embodiment.
[0037] Figure 8 for Figure 7 Cross-sectional view along the a-a' direction;
[0038] Figure 9 A top view schematic diagram of the red and green quantum dot solutions filling the hollowed-out microchannels in step 9 of the embodiment;
[0039] Figure 10 A cross-sectional schematic diagram of the red and green quantum dot solutions filling the hollowed-out microchannels in step 9 of the embodiment;
[0040] Figure 11 This is a schematic diagram of step 9 of the embodiment, where quantum dots are concentrated and deposited on a glass groove array.
[0041] Figure 12 This is a schematic diagram of the quantum dot color conversion layer substrate after the hollowed-out microchannels are peeled off in step 9 of the embodiment.
[0042] Figure 13 This is a schematic diagram of the filter encapsulation layer in step 10 of the embodiment;
[0043] Figure 14 This is a schematic diagram of the flip-chip Micro-LED chip array in step 11 of the embodiment;
[0044] Figure 15 This is a schematic diagram of the structure of the Micro-LED full-color display device obtained in the embodiment. Detailed Implementation
[0045] The present invention will be further explained below with reference to the accompanying drawings and specific embodiments. The accompanying drawings are merely illustrative to facilitate a better understanding of the invention, and their specific proportions can be adjusted according to design requirements.
[0046] This embodiment employs open microfluidic technology to fabricate perforated glass microchannels suitable for quantum dot solution deposition. The "liquid-repellent" properties of the relevant groups in the liquid-repellent chemical substances restrict the flow of the quantum dot solution, allowing the quantum dot solvent to evaporate and concentrate in a patterned groove array. Micro-LED blue light excites the quantum dot pattern in the grooves, enabling full-color display. It mainly consists of four parts:
[0047] I. Fabrication of a patterned glass groove array using a metal mask. A metal layer is etched on the surface of a transparent substrate using photoresist as a mask, and then transparent glass is etched using the metal layer as a mask to form a patterned glass groove array with quantum dot pre-deposition. The surface outside the groove array is then treated with a liquefaction effect using photoresist as a mask to form a groove array with two different wettabilities on the inner and outer surfaces.
[0048] II. Glass Microchannel Design. A laser is used to scan the glass surface to create microchannel outlines, altering the surface properties along the scanning path. Hydrofluoric acid is then used to selectively remove glass along the laser scanning path, resulting in glass with a microchannel pattern. Fluorine-containing molecules are then added to the glass surface via wet / dry deposition to impart hydrophobic properties. The width of the microchannels corresponds one-to-one with the width of the patterned groove array, with the width at bends being one-third of the patterned array width, facilitating connectivity between different rows of quantum dot arrays.
[0049] III. Quantum Dot Solution Deposition. Appropriate amounts of red and green quantum dot solutions are dropped into the inlet of each channel, flowing into the microchannels and groove array via capillary wetting. As the solvent evaporates, the quantum dot concentration gradually increases. Due to the hydrophobic molecular modification of the microchannel glass surface and the outer surface of the groove array, the quantum dot solution is more easily deposited within the hydrophilic grooves, ultimately achieving deposition within the grooves. Because the microchannels are perforated substrates in contact with air, the solvent evaporation rate of the quantum dots is rapid, and the quantum dot concentration gradually increases with solvent evaporation, facilitating solute deposition into the glass groove array. Due to the different surface compositions inside and outside the groove structure, the high-concentration quantum dot solution ultimately selectively deposits within the grooves, thus allowing for a simple and spontaneous acquisition of quantum dot arrays. Since the microchannels are independent, quantum dots of different thicknesses and colors can be deposited simultaneously and rapidly to prepare quantum dot color conversion layers for full-color displays.
[0050] IV. Filter Encapsulation Layer Design. To prevent light crosstalk and improve color purity, three patterned filter layers corresponding one-to-one with the bottom sub-pixels are deposited on the surface of a transparent glass substrate, and a matrix photoresist with a black matrix is deposited between each filter layer through photolithography.
[0051] Example 1
[0052] Step 1. Cleaning the transparent glass substrate. Soak the transparent glass substrate in acetone solution for 20 minutes, then clean it with ethanol solution, and finally rinse it with deionized water for 3-5 minutes. Place it in an oven at 70℃ and dry it for 5-10 minutes to thoroughly remove surface moisture.
[0053] Step 2. Metal mask layer deposition. A 20nm-50nm metal layer that can serve as a mask is deposited on the surface of the first glass substrate 11 using methods such as electron beam thin film deposition, thermal evaporation deposition, or magnetron sputtering thin film deposition. In this embodiment, a chromium layer 12 is deposited as the mask layer using a thermal evaporation thin film deposition system. The deposition rate is set to 20A / s, the gas pressure to 5Pa, the substrate rotation speed to 50rpm, and the chromium layer 12 with a thickness of 30nm is deposited to form the first substrate 1. The cross-sectional view is shown below. Figure 1 As shown.
[0054] Step 3. Patterning the metal mask layer. Photoresist is spin-coated onto the surface of the chromium layer 12. A patterned photoresist is formed through pre-baking, exposure, reverse baking, over-exposure, and development, resulting in an array of openings. The exposed chromium layer 12 is etched using an etching solution composed of cerium ammonium nitrate, 98% acetic acid solution, and deionized water for 2-3 minutes, followed by rinsing with deionized water for 5 minutes to remove the photoresist, yielding the patterned first substrate 1. The chromium layer 12 has an array of openings, with the bottom of the openings exposing the first glass substrate 11. A top view is shown below. Figure 2 As shown.
[0055] Step 4. Fabrication of the patterned glass groove array. Using the patterned chromium layer 12 as a mask, the first glass substrate 11 is etched with hydrofluoric acid solution for 3-4 minutes. The etched patterned first substrate 11 is then rinsed in deionized water for 5-10 minutes and placed in a 100℃ oven to thoroughly remove moisture. This process creates an array of grooves 11a on the surface of the first glass substrate 11. The depth of the grooves 11a is 2-10 μm, and their cross-sectional view is shown below. Figure 3 As shown.
[0056] Step 5. Fill the groove array with photoresist. Apply photoresist to the patterned surface of the first substrate 1 prepared in step 4. Through baking, overlaying, exposure, and development, the photoresist R1 fills the groove array, thus masking the groove 11a. A top view is shown below. Figure 4As shown.
[0057] Step 6. Hydrophobic chemical surface modification. Using photoresist R1 as a mask, the patterned first substrate 1 is placed in a reaction vessel with a trichloro(1H,1H,2H,2H-tridecylfluoron-octyl)silane atmosphere and reacted in a 60°C oven for 2-3 hours to change the adsorption of liquid on the chromium layer surface. Then, the substrate is placed in an ethanol solution and sonicated for 5 minutes to completely remove the photoresist R1 in the groove, forming two regions with different chemical properties: the inner wall of the groove 11a is hydrophilic, and the surface of the chromium layer on the substrate is hydrophobic.
[0058] Step 7. Laser-induced fabrication of hollowed-out microchannels. A second glass substrate 2 with a thickness of 450 μm is provided, and a picosecond laser is used to fabricate the hollowed-out microchannels. Figure 5 Laser-induced glass modification was performed along the designed route, with a laser pulse energy of 24 μJ, a laser scanning speed of 1 mm / s, a pulse width of 4 wfs, and a dot pitch of 5 μm. The laser-treated second glass substrate 2 was then immersed in a hydrofluoric acid solution for etching for 3-4 minutes, ensuring complete etching of the modified glass area and forming a hollow microchannel 2a connecting the front and back sides of the glass. Figure 6 As shown. Specifically, the microchannel 2a includes several arranged strip channels 211, with each pair of strip channels 211 forming a unit. A space for one strip channel is left between adjacent units. The strip channels of adjacent units are connected pairwise by curved channels 212. That is, one end of the strip channel in the middle unit is connected to the unit above, and the other end is connected to the unit below, thus forming a microchannel pathway that is connected end-to-end. Two microchannel pathways run parallel. The width of the strip channel 211 matches the width of the groove 11a, ranging from 40 to 100 micrometers, and its length is sufficient to cover the row length of the groove array. The width of the curved channel 212 is 1 / 3 the width of the strip channel 211.
[0059] Step 8. Substrate Bonding. Using a dedicated laminator, the chemically modified patterned first substrate 1 and the second glass substrate 2 are aligned one-to-one using the array as alignment marks and bonded together. The two substrates are then clamped together using jigs to ensure a tight bond. A top view of the precise bonding is shown below. Figure 7 As shown, the cross-sectional view is as follows Figure 8 As shown, each of the linear channels 211 corresponds to a row of grooves 11a.
[0060] Step 9. Quantum Dot Pattern Deposition. Using a fine glass needle, inject red quantum dot solution R and green quantum dot solution G into their respective microchannel pathways until the quantum dot solution fills the entire microchannel pathway, thus also filling the corresponding groove array, as shown below. Figure 9 and Figure 10As shown. Since the microchannel pathway is an open channel, the quantum dot solvent evaporates naturally. Because the chromium layer on the surface of the patterned first substrate 1 is hydrophobic, while the inner wall of the groove is hydrophilic, during solvent evaporation, the quantum dot solution continuously tends to enter the groove 11a. After the solvent has completely evaporated, the quantum dots are concentrated only in the glass groove array to form quantum dot units, as shown. Figure 11 As shown. In this embodiment, the thickness of a single deposition can reach 2-10 micrometers. After peeling off the second glass substrate 2, a quantum dot color conversion layer substrate with patterned deposition of red quantum dots R / green quantum dots G is formed, as shown. Figure 12 As shown, the grooves where no quantum dot solution is deposited serve as blue light transmission region B.
[0061] Step 10. Fabrication of the filter encapsulation layer. First, red, green, and blue photoresist layers are sequentially patterned and deposited on a transparent third glass substrate 3 to form an array of red filter 3R / green filter 3G / blue filter 3B. Then, black photoresist is prepared between the color photoresist layers through photolithography, pre-baking, exposure, reverse baking, overexposure, development, and high-temperature hard baking as a masking layer 31. The patterns of each photoresist layer are separated by a black photoresist matrix. The red filter 3R passes through a wavelength range of 620-650nm, the green filter 3G passes through a wavelength range of 510-540nm, and the blue filter 3B passes through a wavelength range of 450-470nm. Figure 13 As shown.
[0062] Step 11. Fabrication of Flip-Chip Blue Micro-LED Light-Emitting Chip Array. On a single-layer polished patterned sapphire substrate, a GaN thin film epitaxial layer is deposited sequentially via metal-organic chemical vapor deposition (MOCVD). Then, a flip-chip blue micro-LED light-emitting chip array 4 is fabricated through semiconductor processes including photolithography, etching, deposition, sputtering, and bonding. This array is bonded to the bottom driving substrate. A black photoresist barrier 42 is established in each blue light-emitting unit 41 using spin-coating of a black matrix photoresist combined with etching to reduce light crosstalk between sub-pixels. Figure 14 As shown.
[0063] Step 12. Bonding of the filter encapsulation layer, blue Micro-LED light-emitting array, and quantum dot color conversion layer substrate. The filter encapsulation layer is bonded to the pre-deposited red and green quantum dot color conversion layer substrate using a bonding machine, and then bonded one by one to the sub-pixels of the blue Micro-LED light-emitting array, as shown below. Figure 15 As shown, the fabrication of a Micro-LED full-color display device is realized.
[0064] refer to Figure 15The resulting Micro-LED full-color display device comprises, from bottom to top, a blue Micro-LED light-emitting chip array 4, a quantum dot color conversion layer, and a filter encapsulation layer. The blue Micro-LED light-emitting chip array 4 includes an array of blue light-emitting units 41 and black photoresist barriers 42 positioned between adjacent blue light-emitting units 41. The quantum dot color conversion layer includes a patterned first substrate 1, with red quantum dots R, green quantum dots G, and blue light-transmitting regions B formed in a groove array, corresponding one-to-one with the blue light-emitting units 41. The filter encapsulation layer includes a third glass substrate 3 and an array of red, green, and blue filters 3R, 3G, and 3B disposed on the bottom surface of the third glass substrate 3, corresponding one-to-one with the quantum dot units and in corresponding colors. The filter layers are separated by black photoresist 31. Thus, the light emitted by the blue light-emitting units 41 passes through the color conversion layer and the filters to form a three-primary-color display.
[0065] The above embodiments are only used to further illustrate the method for preparing Micro-LED full-color display devices based on open microfluidic technology of the present invention. However, the present invention is not limited to the embodiments. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for fabricating a Micro-LED full-color display device based on open microfluidic technology, characterized in that: A quantum dot color conversion layer and a filter encapsulation layer are fabricated, and the two sides of the quantum dot color conversion layer are bonded to a Micro-LED light-emitting chip array and a filter encapsulation layer, respectively; wherein the fabrication of the quantum dot color conversion layer includes the following steps: 1) Fabricating a transparent groove array on a first substrate; the first substrate includes a first glass substrate and a metal mask layer disposed on the first glass substrate, the metal mask layer being a chromium layer with a thickness of 20nm-50nm; the fabrication of the groove array includes: 1.1) The metal mask layer is patterned using etching technology to form an array of openings; 1.2) Using a patterned metal mask layer as a mask, the first glass substrate is etched to form the transparent groove array; 2) Fill the groove array with photoresist, place the first substrate in a reaction vessel under a trichloro(1H,1H,2H,2H-tetrafluorooctyl)silane atmosphere, react at 50~70°C for 2-3 hours, modify the chromium layer surface to be hydrophobic, and then remove the photoresist to perform hydrophobic treatment on the surface outside the groove array of the first substrate. 3) Provide a second substrate, and form a hollowed-out microchannel in the second substrate; the hollowed-out microchannel includes a plurality of strip channels arranged in a row, with each pair of strip channels forming a unit, and a space of one strip channel left between adjacent units. The strip channels of adjacent units are connected in pairs through curved channels to form two parallel microchannel pathways. 4) Bond the first substrate and the second substrate together so that each strip channel corresponds to a row of grooves in the groove array to form a microchannel pathway; 5) Fill one of the two microchannels with red quantum dot solution and the other with green quantum dot solution. During the evaporation of the quantum dot solution, it gradually deposits in the groove to form quantum dot units. 6) Peel off the second substrate; The filter encapsulation layer is prepared by forming a filter array on a third substrate, wherein the filter array corresponds one-to-one with the groove array, and a shielding layer is provided between adjacent filters.
2. The method for fabricating a Micro-LED full-color display device based on open microfluidic technology according to claim 1, characterized in that: The depth of the groove is 2-10 μm.
3. The method for fabricating a Micro-LED full-color display device based on open microfluidic technology according to claim 1, characterized in that: The second substrate is a glass substrate. In step 3), a femtosecond laser is first used to laser-induced denaturation of the microchannel wiring preset area of the second substrate, and then the second substrate is etched in hydrofluoric acid solution to form the hollowed-out microchannel.
4. The method for fabricating a Micro-LED full-color display device based on open microfluidic technology according to claim 3, characterized in that: The thickness of the second substrate is 350-550 micrometers, the pulse energy of the femtosecond laser is 10-50 μJ, the laser scanning speed is 1-3 mm / s, the pulse width is 2-5 wfs, and the dot pitch is 3-8 μm.
5. The method for fabricating a Micro-LED full-color display device based on open microfluidic technology according to claim 1, characterized in that: The width of the strip channel matches the width of the groove, and its length covers the row length of the groove array. The width of the curved channel is 20% to 50% of the width of the strip channel.
6. The method for fabricating a Micro-LED full-color display device based on open microfluidic technology according to claim 1, characterized in that: The Micro-LED light-emitting chip array is a blue light-emitting chip.
Citation Information
Patent Citations
Quantum dot color conversion layer and preparation method and application thereof
CN114597302A
High-quality Micro-LED full-color display device based on microfluidic technology and preparation method
CN115763518A
Preparation method and application of thickness-controllable quantum dot color conversion layer
CN116364834A
